Discourse of Self and Other in Landscape by Harold Pinter - Avantika Johri (Emerging Trends in Languages, 2024)
This paper explores Harold Pinter’s Landscape as a pivotal representation of the complex dynamics between the subjective self and social reality. It investigates how the characters' introspection blurs the line between objective and subjective truths, highlighting their disillusionment with present-day existence and their reliance on past memories for solace. Through a dialectic discourse, Pinter’s characters reconstruct their identities and relationships, presenting fragmented versions of truth that reveal the unreliability of perception and the challenges of communication. The play's intense focus on the stream of consciousness demonstrates how memory, perception, and social structures influence the understanding of self and others, particularly in the context of gender dynamics. Beth's introspective, refined dialogue contrasts with Duff’s coarse pragmatism, emphasizing the divergent ways they navigate their shared past. The paper situates Landscape within the broader Pinterian canon, examining its treatment of class, social roles, and gender relations, while also comparing its approach to other memory plays by Pinter and his contemporaries. It also explores the concept of solitude, examining how the individuals' inner monologues function as a haven and a hindrance to real connection. Ultimately, the paper underscores how Landscape dissects human relationships, showing how self-awareness and the need for self-definition collide with the desire for connection and recognition from the other.
Keywords: Harold Pinter; gender dynamics; memory plays; stream of consciousness; subjective vs objective reality